IMPROVING THE METHODOLOGY FOR DEVELOPING STUDENTS’ PROFESSIONAL COMPETENCE IN THE CONTEXT OF DIGITALIZATION - Tadiboyev Kamoldin Abdusadikovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: In today’s rapidly advancing process of globalization and integration, it is crucial to educate future specialist professionals studying in higher education institutions in accordance with modern requirements and in harmony with the times. It is equally important to teach them how to freely utilize advanced innovative developments. The final sentence "Now translate it into English" appears to be an instruction and should not be included in the translation. This article proposes issues of developing media literacy among future young professionals in the context of today’s digital information exchange and adapting them to today’s digital age. By actively integrating digital tools into the educational process, future specialists will have the opportunity to work effectively and productively in their chosen fields of activity, develop critical thinking skills, and learn to quickly exchange and analyze information. The skills they acquire enable them to easily master modern advanced methods, which are of paramount importance in the educational process, and to effectively apply them in practice in today’s rapidly changing digital world.